German immigrants in central Poland in the late 18th and early 19th centuries - Marszał, Tadeusz (European Spatial Research and Policy, 2022)
The aim of this article is to provide a holistic presentation of the genesis, intensity, and directions of movement, as well as the spatial and temporal distribution of the German national group which settled in Central Poland from the end of the 18th century to the 1820–1830 period. This paper analyses the determinants of the inflow of German immigrants, and their geographical origin, as well as the social and occupational structure. The settlers from German lands were a very diverse social group. In the case of first and second-generation immigrants who came to Central Poland, the social integration process was still quite slow. The colonists and settlers living in the diaspora developed a certain pattern of existence that focused on their immediate environment separating them from the outside world, while the retention of their mother tongue and religious tradition was more an expression of traditionalist consciousness than national identity.